Determination of controlling fouling mechanism using the Hermia models and estimation of the manufacturing costs of the modified polyvinylidene fluoride-based ultrafiltration membranes - Saleem, Abdullah G.; Al-Jubouri, Sama M.; Al-Batty, Sirhan; Wali Hakami, Mohammed (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Membrane fouling is the main problem that limits the use of membrane technology. This work focuses on using the Hermia models to determine the controlling fouling mechanisms, including intermediate pore blocking, complete pore blocking, standard pore blocking, and cake formation. Also, it investigates the estimation of the manufacturing costs, which included the costs of preparation materials and energy consumed during the preparation and casting processes of the polyvinylidene fluoride/polyethylene glycol (PVDF/PEG) and PVDF/PEG-tin oxide nanoparticles (PVDF/PEG-SnO2 NPs) membranes. The results of Hermia’s models were applied on the first, third, and fifth cycles of the rhodamine B dye solution filtration processes. Depending on linear fitting parameters, the membrane fouling occurred in all fouling mechanism types simultaneously. However, the predominating fouling mechanism was cake formation followed by intermediate pore blocking. Analysis of the parameters of the fouling models validated that the irreversible fouling exceeded the reversible fouling when the correlation factor (R2) value was higher than 0.95, which explains the continuous reduction of the permeate flux for both studied membranes. The estimated cost of the locally manufactured PVDF-based membranes did not surpass 80 $/m2 of the membrane. Also, the locally fabricated flat sheet ultrafiltration membranes are cheaper than other pristine PVDF membranes manufactured by Guochukeji Technology (Xiamen) Company.